Sulfur-resistant CO-resistant high-entropy intermetallic compound catalyst as well as preparation method and application thereof

A high-entropy intermetallic compound catalyst that is resistant to sulfur and CO resistant to CO is prepared by uploading Ni-Co-Cu-Fe-In-M six-metallic compound on aluminum-magnesium metal mixed oxides and introducing additive elements Zn, Mo or Ce. The problem of existing catalysts not suitable for use in CO-rich atmosphere and insufficient sulfur resistance is solved, high conversion rate and excellent sulfur resistance are achieved, and a new industrial design is provided for green methanol synthesis.

CN119281336APending Publication Date: 2025-01-10EAST CHINA UNIV OF SCI & TECH +1
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411385477.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing methanol synthesis catalysts are not suitable for use in a CO-rich atmosphere, and have insufficient sulfur resistance, making it difficult to adapt to the process needs of green methanol production.

Method used

Develop a sulfur-resistant CO-resistant high entropy intermetallic compound catalyst, which is supported by Ni-Co-Cu-Fe-In-M six-metallic intermetallic compound on aluminum-magnesium metal mixed oxides and is subjected to co-precipitation and thermal reduction treatment. Preparation, the additive elements Zn, Mo or Ce are introduced to enhance the sulfur resistance of the catalyst.

Benefits of technology

The catalyst exhibits excellent CO resistance and high conversion rate under a CO-rich atmosphere, and significantly improves sulfur resistance by introducing additive elements, overcomes the problems of insufficient CO resistance and sulfur resistance of existing catalysts, and is green Methanol synthesis provides new industrial design ideas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119281336A_ABST
    Figure CN119281336A_ABST
Patent Text Reader

Abstract

The invention discloses a sulfur-resistant CO-resistant high-entropy intermetallic compound catalyst as well as a preparation method and application thereof. The catalyst is a Ni-Co-Cu-Fe-In-M high-entropy intermetallic compound catalyst obtained by loading a Ni-Co-Cu-Fe-In-M six-membered intermetallic compound on an aluminum-magnesium metal mixed oxide, wherein Ni, Co, Cu and Fe are active metals, In is an inert metal, and M is a sulfur-resistant metal and is selected from one of Zn, Mo and Ce; according to the catalyst, the structural characteristics of LDH are utilized, meanwhile, by means of the synergistic effect of multiple elements in the high-entropy intermetallic compound catalyst, the catalyst has excellent CO resistance, the sulfur resistance of the catalyst is remarkably improved by introducing the auxiliary element M, meanwhile, high conversion rate and high selectivity are taken into consideration, and the catalyst is suitable for industrial production. The technical bottleneck that the existing catalyst is insufficient in CO resistance and sulfur resistance is overcome, and a brand new thought is provided for industrial design of a green methanol synthesis catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of catalysts, and in particular relates to a sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst and a preparation method and application thereof. Background Art

[0002] As a basic chemical raw material, methanol occupies an important position in downstream industries, especially in the production of organic solvents and synthetic fibers. In addition, in the energy field, methanol is a clean liquid fuel. Compared with traditional fossil fuels, the use of methanol can reduce carbon dioxide emissions by about 60%. However, in the context of the "dual carbon" goal, methanol production faces severe challenges in green transformation. Although coal-to-methanol was once one of the main production routes, its high carbon dioxide emissions have limited its development and made it difficult to adapt to the current low-carbon requirements. Therefore, the development of a green methanol production route with low carbon emissions is of great practical significance for achieving the "dual carbon" goal, and has attracted widespread attention from industry and academia.

[0003] The International Energy Agency has recognized a green methanol production path based on the use of biomass energy, which is: anaerobic fermentation of biomass produces biogas, which is then catalytically reformed to produce synthesis gas after purification and pretreatment (mainly desulfurization process); the synthesis gas is then catalytically hydrogenated to produce methanol. However, most existing methanol synthesis catalysts are only suitable for pure CO 2 The process of hydrogenation to methanol is not suitable for direct use in synthesis gas (CO in a CO atmosphere). 2 ) is hydrogenated to produce methanol. In addition, trace amounts of H 2 Residual sulfur puts forward higher requirements on the sulfur resistance of the catalyst. Therefore, in order to realize the large-scale production of green methanol, it is urgent to develop a methanol synthesis catalyst with high activity, high selectivity, CO resistance and excellent sulfur resistance to meet the process requirements of green methanol production.

[0004] High entropy metal catalysts are composed of five or more elements, which can form abundant surface active sites and show excellent catalytic performance and thermal stability. In addition, their diversified composition allows for a large room for regulation of catalytic performance, which can meet the dual requirements of methanol synthesis catalysts for CO resistance and sulfur resistance. Layered double hydroxides (LDHs) are ideal materials for the preparation of high entropy metal catalyst precursors due to their advantages such as adjustable main layer composition and easy exchange of intercalated anions, and provide an effective synthetic route for catalyst modification. Summary of the invention

[0005] In order to solve the above problems in the prior art, the present invention provides a sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst and a preparation method and application thereof. The present invention utilizes the structural characteristics of LDH and successfully develops a series of Ni-Co-Cu-Fe-In-M (M = Zn, Mo or Ce) catalysts. With the synergistic effect between multiple elements in the high-entropy intermetallic compound catalyst, it has excellent CO resistance, and by introducing the auxiliary element M, the sulfur resistance of the catalyst is significantly improved, while taking into account high conversion rate and high selectivity, overcoming the technical bottleneck of insufficient CO resistance and sulfur resistance of existing catalysts, and providing a new idea for the industrial design of green methanol synthesis catalysts.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] The first aspect of the present invention is to provide a sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst, wherein the catalyst is a Ni-Co-Cu-Fe-In-M high-entropy intermetallic compound catalyst obtained by loading a Ni-Co-Cu-Fe-In-M hexametallic compound on an aluminum-magnesium metal mixed oxide;

[0008] Among them, Ni, Co, Cu and Fe are active metals, In is an inert metal, and M is a sulfur-resistant metal selected from one of Zn, Mo and Ce;

[0009] The molar ratio of the metals Ni, Co, Cu, Fe, In, M, Mg and Al in the catalyst is 1:(0.9-1.1):(0.9-1.1):(0.9-1.1):(0.9-1.1):(0.9-1.1):(14-16):(4-6), preferably 1:1:1:1:1:1:(14-16):(4-6).

[0010] It should be noted that the inert metal refers only to the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst prepared in the present invention, relative to the active metal, in the CO rich atmosphere. 2 It is inert during hydrogenation.

[0011] The second aspect of the present invention is to provide a method for preparing the above-mentioned sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst, comprising the following steps:

[0012] (1) Preparation of Ni / Co / Cu / Fe / In / M / Mg / Al octal layered hydroxide

[0013] When M is Zn or Ce, nitrates of Ni, Co, Cu, Fe, In, M, Mg and Al are prepared into a mixed metal nitrate solution in proportion, and then a Ni / Co / Cu / Fe / In / M / Mg / Al octal layered hydroxide is prepared by a coprecipitation method;

[0014] When M is Mo, nitrates of Ni, Co, Cu, Fe, In, Mg and Al are prepared into a mixed metal nitrate solution in proportion, and a Ni / Co / Cu / Fe / In / Mg / Al seven-membered layered hydroxide is prepared by a coprecipitation method; then a Mo precursor solution is added to the seven-membered layered hydroxide for ion exchange to prepare a Ni / Co / Cu / Fe / In / M / Mg / Al eight-membered layered hydroxide;

[0015] (2) The Ni / Co / Cu / Fe / In / M / Mg / Al octa-layered hydroxide in step (1) is filtered, washed and dried, and then subjected to thermal reduction treatment to obtain a sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst.

[0016] According to the present invention, in step (1), when M is Zn or Ce, the molar ratio of Ni, Co, Cu, Fe, In, M, Mg and Al ions in the mixed metal nitrate solution is 1:(0.9-1.1):(0.9-1.1):(0.9-1.1):(0.9-1.1):(0.9-1.1):(14-16):(4-6); preferably, the molar ratio of Ni, Co, Cu, Fe, In, M, Mg and Al ions in the mixed metal nitrate solution is 1:1:1:1:1:1:(14-16):(4-6);

[0017] When M is Mo, the molar ratio of Ni, Co, Cu, Fe, In, Mg and Al ions in the mixed metal nitrate solution is 1:(0.9-1.1):(0.9-1.1):(0.9-1.1):(0.9-1.1):(14-16):(4-6); preferably, the molar ratio of Ni, Co, Cu, Fe, In, Mg and Al ions in the mixed metal nitrate solution is 1:1:1:1:1:(14-16):(4-6); the molar ratio of Ni ions in the mixed metal nitrate solution to molybdate ions in the Mo precursor solution is 1:(0.9-1.1).

[0018] According to the present invention, in step (1), the nitrates of Ni, Co, Cu, Fe, In, Zn, Ce, Mg and Al are respectively Ni(NO 3 ) 2 6H 2 O、Co(NO 3 )2 6H 2 O, Cu(NO 3 ) 2 ·3H 2 O, Fe(NO 3 ) 3 9H 2 O、In(NO 3 ) 3 、Zn(NO 3 ) 2 6H 2 O、Ce(NO 3 ) 2 6H 2 O、Mg(NO 3 ) 2 6H 2 O and Al(NO 3 ) 3 9H 2 O; the Mo precursor is selected from Na 2 MoO 4 , K 2 MoO 4 or (NH 4 ) 2 MoO 4 One of;

[0019] In the mixed metal nitrate solution, the concentration of Mg ions is 0.40-0.65 mol / L; in the Mo precursor solution, the concentration of Mo ions is 0.08-0.12 mol / L.

[0020] According to the present invention, step (1) specifically comprises the following steps:

[0021] Under stirring conditions, when M is Zn or Ce, a mixed metal nitrate solution is added to the precipitant, or when M is Mo, a mixed metal nitrate solution and a Mo precursor solution are added to the precipitant in sequence, the feeding rate is controlled to be 0.8-1.2 mL / min, the temperature of the reaction system is controlled to be 60-70° C., and the pH value of the reaction system is controlled to be 10±1 by a pH regulator; after the feeding is completed, the stirring reaction is continued for 15-20 hours to obtain the Ni / Co / Cu / Fe / In / M / Mg / Al octal layered hydroxide.

[0022] According to the present invention, the precipitant is selected from Na 2 CO 3 Solution, NaHCO 3 Solution or K 2 CO 3 A solution; the molar concentration of the precipitant is 0.3-0.5 mol / L.

[0023] According to the present invention, the pH regulator is selected from one of a NaOH solution and a KOH solution; the molar concentration of the pH regulator is 1.8 to 2.0 mol / L.

[0024] According to the present invention, in step (2), the drying conditions are: 90-110°C, drying for 12-20 hours; the thermal reduction treatment conditions are: 2 In a mixed atmosphere with Ar, reduce at 700-900°C for 3-5 hours.

[0025] The third aspect of the present invention is to provide the use of the above-mentioned sulfur-resistant and CO-resistant high-entropy metal compound catalyst for CO in a CO-rich atmosphere. 2 Catalytic hydrogenation to methanol reaction.

[0026] According to the present invention, the catalytic reaction conditions are: the raw gas includes 15-25 ppm H 2 S, 23-27% CO, 4-6% CO 2 , 64~66% H 2 , the remaining gas is N 2 ; The reaction temperature is 200-300°C; The pressure is 3-5MPa.

[0027] The technical effects of the present invention are as follows:

[0028] (1) The present invention broadens the existing CO 2 The application scope of hydrogenation methanol catalyst is to use the synergistic effect between multiple elements in high entropy metal compound catalyst to make the catalyst have excellent CO resistance and is suitable for CO in CO-rich atmosphere. 2 Application scenario of hydrogenation to produce green methanol. In this application scenario, in the Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst prepared by the present invention, Cu is good at activating H 2 , Ni, Co and Fe can promote CO and CO 2 The adsorption and decomposition of In can be controlled, while In can isolate other metal atoms and optimize the geometric structure and electronic structure of the active sites, thereby producing a synergistic effect in the catalytic process and improving the overall efficiency and selectivity of the reaction. The synergistic effect originates from the unique electronic structure, geometric structure and abundant active sites formed by the electronic interaction and lattice distortion effect of different metal atoms. The catalyst designed by the present invention successfully utilizes this characteristic to provide new ideas and inspiration for the industrialization of green methanol synthesis.

[0029] (2) The present invention also provides a design idea for improving the sulfur resistance of the catalyst, that is, introducing an additive element M (Zn, Mo or Ce) on the basis of a catalyst with CO resistance, so that it also has excellent sulfur resistance. The success of this design is due to the diversified combination of components, which gives the catalytic performance a large room for regulation. By introducing the element M, the electronic structure of the catalyst can be effectively modified to reduce the H 2 S is strongly adsorbed on the active center; it can also modify the surface structure of the catalyst and reduce H 2 S directly contacts the active site; or element M can contact H 2 S forms stable sulfides (such as MoS 2 ), thereby avoiding sulfur "poisoning" on the catalyst surface. Based on these anti-sulfur mechanisms, element M significantly improves the anti-sulfur performance of the catalyst, effectively solving the process problem of poor sulfur resistance of existing catalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 It is the XRD spectrum of the Ni-Co-Cu-Fe-In-Zn high entropy intermetallic compound catalyst prepared in Example 1 of the present invention.

[0031] Figure 2 This is a stability test chart of the Ni-Co-Cu-Fe-In-Zn high entropy intermetallic compound catalyst prepared in Example 1 of the present invention.

[0032] Figure 3 This is a stability test chart of the Ni-Co-Cu-Fe-In-Mo high entropy intermetallic compound catalyst prepared in Example 2 of the present invention.

[0033] Figure 4 This is a stability test chart of the Ni-Co-Cu-Fe-In-Ce high entropy intermetallic compound catalyst prepared in Example 3 of the present invention.

[0034] Figure 5 This is a stability test chart of the Ni-Co-Cu-Fe-In high entropy intermetallic compound catalyst prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0035] The present invention is described clearly and in detail by specific embodiments in conjunction with the accompanying drawings. It should be understood that the following embodiments are only part of the embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should be included in the scope of protection of the present invention.

[0036] Unless otherwise specified, the instruments and equipment used in the following examples are conventional devices in the art. The experimental conditions not specified are usually those recommended by the manufacturer or conventional conditions. The reagents and materials used are conventional commercially available products.

[0037] Example 1. Preparation of Ni-Co-Cu-Fe-In-Zn high entropy intermetallic compound catalyst

[0038] (1) 0.8724 g Ni(NO 3 ) 2 6H 2 O, 0.8731 g Co(NO 3 ) 2 6H 2 O, 0.7248 g Cu(NO 3 ) 2 ·3H 2 O, 1.2117 g Fe(NO 3 ) 3 9H 2 O, 0.9025g In(NO 3 ) 3 、0.8925g Zn(NO 3 ) 2 6H 2 O, 11.5385gMg(NO 3 ) 2 6H 2 O and 5.6270gAl(NO 3 ) 3 9H 2 O was dissolved in 100 mL of ultrapure water and dispersed by ultrasonic, which was recorded as the mixed metal nitrate solution; 4.24 g Na 2 CO 3 The powder was dissolved in 100 mL of ultrapure water and ultrasonically dispersed to obtain the desired precipitant; 15.00 g of NaOH powder was dissolved in 200 mL of ultrapure water and ultrasonically dispersed to obtain the desired pH regulator;

[0039] The precipitant was transferred to a 500 mL three-necked flask and placed in an oil bath at 65°C for constant temperature treatment for 1 hour; then the mixed metal nitrate solution was added dropwise to the three-necked flask at a rotation speed of 100 r / min, and a constant flow pump was used to control its flow rate to 1.0 mL / min; at the same time, a pH regulator was added using a constant flow pump to control the pH of the reaction system in the three-necked flask to be constant at 10.0; after the feeding was completed, continuous and vigorous stirring was continued at a synthesis temperature of 65°C for 18 hours, and then vacuum filtered and washed several times until the pH was neutral to obtain a grass green block solid.

[0040] (2) The grass green block solid obtained in step (1) is dried at 100° C. for 16 hours and then fully mechanically ground to obtain a Ni / Co / Cu / Fe / In / Zn / Mg / Al octa-layered hydroxide, labeled as W1.

[0041] (3) The octavalent layered hydroxide W1 of step (2) is heated at 800°C in H 2 The catalyst was reduced in a mixed atmosphere of argon and Ar (volume ratio 1:4) for 4 hours to obtain a Ni-Co-Cu-Fe-In-Zn high entropy intermetallic compound catalyst, and its XRD spectrum is shown in FIG. Figure 1 As shown, the molar ratio of Ni, Co, Cu, Fe, In and Zn in the catalyst is 1:1:1:1:1:1.

[0042] Example 2: Preparation of Ni-Co-Cu-Fe-In-Mo high entropy intermetallic compound catalyst

[0043] (1) 0.8724 g Ni(NO 3 ) 2 6H 2 O, 0.8731 g Co(NO 3 ) 2 6H 2 O, 0.7248 g Cu(NO 3 ) 2 ·3H 2 O, 1.2117 g Fe(NO 3 ) 3 9H 2 O, 0.9025g In(NO 3 ) 3 、11.5385g Mg(NO 3 ) 2 6H 2 O and 5.6270g Al(NO 3 ) 3 9H 2 O was dissolved in 70 mL of ultrapure water and dispersed by ultrasonic, which was recorded as mixed metal nitrate solution; 0.6178 g Na 2 MoO 4 Dissolve in 30 mL ultrapure water and disperse by ultrasonic, record as sodium molybdate solution; 4.24 g Na 2 CO 3 The powder was dissolved in 100 mL of ultrapure water and ultrasonically dispersed to obtain the desired precipitant; 15.00 g of NaOH powder was dissolved in 200 mL of ultrapure water and ultrasonically dispersed to obtain the desired pH adjuster;

[0044] The precipitant was transferred to a 500 mL three-necked flask and placed in an oil bath at 65°C for constant temperature treatment for 1 hour; then, the mixed metal nitrate solution and the sodium molybdate solution were added dropwise to the three-necked flask at a rotation speed of 100 r / min, and the flow rate was controlled to 1.0 mL / min using a constant flow pump; at the same time, a pH regulator was added using a constant flow pump to control the pH of the reaction system in the three-necked flask to be constant at 10.0; after the feeding was completed, continuous and vigorous stirring was continued at a synthesis temperature of 65°C for 18 hours, and then vacuum filtered and washed several times until the pH was neutral to obtain a dark green block solid.

[0045] (2) The dark green block solid obtained in step (1) is dried at 100° C. for 16 hours and then fully mechanically ground to obtain Ni / Co / Cu / Fe / In / Mo / Mg / Al octa-layered hydroxide, labeled as W2.

[0046] (3) The octavalent layered hydroxide W2 of step (2) is heated at 800°C in H 2 The catalyst was reduced in a mixed atmosphere of N,N-, and Ar (volume ratio of 1:4) for 4 hours to obtain a Ni-Co-Cu-Fe-In-Mo high entropy intermetallic compound catalyst, in which the molar ratio of Ni, Co, Cu, Fe, In and Mo was 1:1:1:1:1:1.

[0047] Example 3. Preparation of Ni-Co-Cu-Fe-In-Ce high entropy intermetallic compound catalyst

[0048] (1) 0.8724 g Ni(NO 3 ) 2 6H 2 O, 0.8731 g Co(NO 3 ) 2 6H 2 O, 0.7248 g Cu(NO 3 ) 2 ·3H 2 O, 1.2117 g Fe(NO 3 ) 3 9H 2 O, 0.9025g In(NO 3 ) 3 、1.3027g Ce(NO 3 ) 2 6H 2 O, 11.5385 g Mg(NO 3 ) 2 6H 2 O and 5.6270gAl(NO 3 ) 3 9H 2O was dissolved in 100 mL of ultrapure water and dispersed by ultrasonic, which was recorded as the mixed metal nitrate solution; 4.24 g Na 2 CO 3 The powder was dissolved in 100 mL of ultrapure water and ultrasonically dispersed to obtain the desired precipitant; 15.00 g of NaOH powder was dissolved in 200 mL of ultrapure water and ultrasonically dispersed to obtain the desired pH regulator;

[0049] The precipitant was transferred to a 500 mL three-necked flask and placed in an oil bath at 65°C for constant temperature treatment for 1 hour; then, the mixed metal nitrate solution was added dropwise to the three-necked flask at a rotation speed of 100 r / min, and a constant flow pump was used to control its flow rate to 1.0 mL / min; at the same time, a pH regulator was added using a constant flow pump to control the pH of the reaction system in the three-necked flask to be constant at 10.0; after the feeding was completed, continuous and vigorous stirring was continued at a synthesis temperature of 65°C for 18 hours, and then vacuum filtered and washed several times until the pH was neutral to obtain a light green block solid.

[0050] (2) The light green block solid obtained in step (1) was dried at 100° C. for 16 hours and then fully mechanically ground to obtain Ni / Co / Cu / Fe / In / Ce / Mg / Al octalayered hydroxide, labeled as W3.

[0051] (3) The octavalent layered hydroxide W3 of step (2) is heated at 800°C in H 2 The catalyst was reduced in a mixed atmosphere of N,N-, and Ar (volume ratio of 1:4) for 4 hours to obtain a Ni-Co-Cu-Fe-In-Ce high entropy intermetallic compound catalyst, in which the molar ratio of Ni, Co, Cu, Fe, In and Ce was 1:1:1:1:1:1.

[0052] Example 4. Preparation of Ni-Co-Cu-Fe-In-Zn high entropy intermetallic compound catalyst

[0053] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:

[0054] In step (1), 0.8724 g Ni(NO 3 ) 2 6H 2 O, 0.7858 g Co(NO 3 ) 2 6H 2 O, 0.6523gCu(NO 3 ) 2 ·3H 2 O, 1.0905 g Fe(NO 3 ) 3 9H 2O, 0.8122g In(NO 3 ) 3 , 0.8032g Zn(NO 3 ) 2 6H 2 O, 11.5385 g Mg(NO 3 ) 2 6H 2 O and 5.6270gAl(NO 3 ) 3 9H 2 O was dissolved in 100 mL of ultrapure water and dispersed by ultrasonic, which was recorded as mixed metal nitrate solution.

[0055] Finally, a Ni-Co-Cu-Fe-In-Zn high entropy intermetallic compound catalyst was obtained, in which the molar ratio of Ni, Co, Cu, Fe, In and Zn was 1:0.9:0.9:0.9:0.9:0.9.

[0056] Example 5. Preparation of Ni-Co-Cu-Fe-In-Mo high entropy intermetallic compound catalyst

[0057] The preparation method of this embodiment is basically the same as that of embodiment 2, except that:

[0058] In step (1), 0.8724 g Ni(NO 3 ) 2 6H 2 O, 0.7858 g Co(NO 3 ) 2 6H 2 O, 0.6523gCu(NO 3 ) 2 ·3H 2 O, 1.0905 g Fe(NO 3 ) 3 9H 2 O, 0.8122g In(NO 3 ) 3 、11.5385g Mg(NO 3 ) 2 6H 2 O and 5.6270gAl(NO 3 ) 3 9H 2 O was dissolved in 70 mL of ultrapure water and dispersed by ultrasonic, which was recorded as mixed metal nitrate solution; 0.5560 g Na 2 MoO 4 The solution was dissolved in 30 mL of ultrapure water and dispersed by ultrasonic, which was recorded as sodium molybdate solution.

[0059] Finally, a Ni-Co-Cu-Fe-In-Mo high entropy intermetallic compound catalyst was obtained, in which the molar ratio of Ni, Co, Cu, Fe, In and Mo was 1:0.9:0.9:0.9:0.9:0.9.

[0060] Example 6. Preparation of Ni-Co-Cu-Fe-In-Ce high entropy intermetallic compound catalyst

[0061] The preparation method of this embodiment is basically the same as that of embodiment 3, except that:

[0062] In step (1), 0.8724 g Ni(NO 3 ) 2 6H 2 O, 0.7858 g Co(NO 3 ) 2 6H 2 O, 0.6523gCu(NO 3 ) 2 ·3H 2 O, 1.0905 g Fe(NO 3 ) 3 9H 2 O, 0.8122g In(NO 3 ) 3 、1.1724g Ce(NO 3 ) 2 6H 2 O, 11.5385 g Mg(NO 3 ) 2 6H 2 O and 5.6270gAl(NO 3 ) 3 9H 2 O was dissolved in 100 mL of ultrapure water and dispersed by ultrasonic, which was recorded as mixed metal nitrate solution.

[0063] Finally, a Ni-Co-Cu-Fe-In-Ce high entropy intermetallic compound catalyst was obtained, in which the molar ratio of Ni, Co, Cu, Fe, In and Ce was 1:0.9:0.9:0.9:0.9:0.9.

[0064] Example 7. Preparation of Ni-Co-Cu-Fe-In-Zn high entropy intermetallic compound catalyst

[0065] The preparation method of this embodiment is basically the same as that of embodiment 1, except that:

[0066] In step (1), 0.8724 g Ni(NO 3 ) 2 6H2 O, 0.9604 g Co(NO 3 ) 2 6H 2 O, 0.7973gCu(NO 3 ) 2 ·3H 2 O, 1.3329 g Fe(NO 3 ) 3 9H 2 O, 0.9927g In(NO 3 ) 3 、0.9817g Zn(NO 3 ) 2 6H 2 O, 11.5385 g Mg(NO 3 ) 2 6H 2 O and 5.6270gAl(NO 3 ) 3 9H 2 O was dissolved in 100 mL of ultrapure water and dispersed by ultrasonic, which was recorded as mixed metal nitrate solution.

[0067] Finally, a Ni-Co-Cu-Fe-In-Zn high entropy intermetallic compound catalyst was obtained, in which the molar ratio of Ni, Co, Cu, Fe, In and Zn was 1:1.1:1.1:1.1:1.1:1.1.

[0068] Example 8. Preparation of Ni-Co-Cu-Fe-In-Mo high entropy intermetallic compound catalyst

[0069] The preparation method of this embodiment is basically the same as that of embodiment 2, except that:

[0070] In step (1), 0.8724 g Ni(NO 3 ) 2 6H 2 O, 0.9604 g Co(NO 3 ) 2 6H 2 O, 0.7973gCu(NO 3 ) 2 ·3H 2 O, 1.3329 g Fe(NO 3 ) 3 9H 2 O, 0.9927g In(NO 3 ) 3 、11.5385g Mg(NO 3 ) 2 6H2 O and 5.6270gAl(NO 3 ) 3 9H 2 O was dissolved in 70 mL of ultrapure water and dispersed by ultrasonic, which was recorded as mixed metal nitrate solution; 0.6795 g Na 2 MoO 4 The solution was dissolved in 30 mL of ultrapure water and dispersed by ultrasonic, which was recorded as sodium molybdate solution.

[0071] Finally, a Ni-Co-Cu-Fe-In-Mo high entropy intermetallic compound catalyst was obtained, in which the molar ratio of Ni, Co, Cu, Fe, In and Mo was 1:1.1:1.1:1.1:1.1:1.1.

[0072] Example 9. Preparation of Ni-Co-Cu-Fe-In-Ce high entropy intermetallic compound catalyst

[0073] The preparation method of this embodiment is basically the same as that of embodiment 3, except that:

[0074] In step (1), 0.8724 g Ni(NO 3 ) 2 6H 2 O, 0.9604 g Co(NO 3 ) 2 6H 2 O, 0.7973gCu(NO 3 ) 2 ·3H 2 O, 1.3329 g Fe(NO 3 ) 3 9H 2 O, 0.9927g In(NO 3 ) 3 、1.4329g Ce(NO 3 ) 2 6H 2 O, 11.5385 g Mg(NO 3 ) 2 6H 2 O and 5.6270gAl(NO 3 ) 3 9H 2 O was dissolved in 100 mL of ultrapure water and dispersed by ultrasonic, which was recorded as mixed metal nitrate solution.

[0075] Finally, a Ni-Co-Cu-Fe-In-Ce high entropy intermetallic compound catalyst was obtained, in which the molar ratio of Ni, Co, Cu, Fe, In and Ce was 1:1.1:1.1:1.1:1.1:1.1.

[0076] Comparative Example 1: Preparation of Ni-Co-Cu-Fe-In high entropy intermetallic compound catalyst

[0077] The specific steps include:

[0078] (1) 0.8724 g Ni(NO 3 ) 2 6H 2 O, 0.8731 g Co(NO 3 ) 2 6H 2 O, 0.7248gCu(NO 3 ) 2 ·3H 2 O, 1.2117 g Fe(NO 3 ) 3 9H 2 O, 0.9025g In(NO 3 ) 3 、11.5385g Mg(NO 3 ) 2 6H 2 O and 5.6270gAl(NO 3 ) 3 9H 2 O was dissolved in 100 mL of ultrapure water and dispersed by ultrasonic, which was recorded as the mixed metal nitrate solution; 4.24 g Na 2 CO 3 The powder was dissolved in 100 mL of ultrapure water and ultrasonically dispersed to obtain the desired precipitant; 15.00 g of NaOH powder was dissolved in 200 mL of ultrapure water and ultrasonically dispersed to obtain the desired pH adjuster;

[0079] The precipitant was transferred to a 500 mL three-necked flask and placed in an oil bath at 65°C for constant temperature treatment for 1 hour; then, the mixed metal nitrate solution was added dropwise to the three-necked flask at a rotation speed of 100 r / min, and a constant flow pump was used to control its flow rate to 1.0 mL / min; at the same time, a pH regulator was added using a constant flow pump to control the pH of the reaction system in the three-necked flask to be constant at 10.0; after the feeding was completed, continuous and vigorous stirring was continued at a synthesis temperature of 65°C for 18 hours, and then vacuum filtered and washed several times until the pH was neutral to obtain a light green block solid.

[0080] (2) The light green block solid obtained in step (1) was dried at 100° C. for 16 hours and then fully mechanically ground to obtain a Ni / Co / Cu / Fe / In / Mg / Al seven-component LDH material, labeled as W4.

[0081] (3) The octavalent layered hydroxide W4 prepared in step (2) is heated at 800°C in H 2 The catalyst was reduced in a mixed atmosphere of N,N,O,3-trichloro-2-nitrogen and Ar (volume ratio 1:4) for 4 hours to obtain a Ni-Co-Cu-Fe-In high entropy intermetallic compound catalyst, in which the molar ratio of Ni, Co, Cu, Fe and In was 1:1:1:1:1.

[0082] Comparative Example 2: Preparation of Co-Cu-Fe-In medium entropy intermetallic compound catalyst

[0083] The preparation method of this comparative example is basically the same as that of comparative example 1, except that:

[0084] In step (1), 0.8731 g Co(NO 3 ) 2 6H 2 O, 0.7248 g Cu(NO 3 ) 2 ·3H 2 O, 1.2117 gFe(NO 3 ) 3 9H 2 O, 0.9025g In(NO 3 ) 3 、11.5385g Mg(NO 3 ) 2 6H 2 O and 5.6270gAl(NO 3 ) 3 9H 2 O was dissolved in 100 mL of ultrapure water and dispersed by ultrasonic, which was recorded as mixed metal nitrate solution.

[0085] Finally, a Co-Cu-Fe-In mesohex metallic compound catalyst was obtained, in which the molar ratio of Co, Cu, Fe and In was 1:1:1:1.

[0086] Comparative Example 3: Preparation of Ni-Cu-Fe-In medium entropy intermetallic compound catalyst

[0087] The preparation method of this comparative example is basically the same as that of comparative example 1, except that:

[0088] In step (1), 0.8724 g Ni(NO 3 ) 2 6H 2 O, 0.7248 g Cu(NO 3 ) 2 ·3H 2 O, 1.2117 gFe(NO 3 ) 39H 2 O, 0.9025g In(NO 3 ) 3 、11.5385g Mg(NO 3 ) 2 6H 2 O and 5.6270gAl(NO 3 ) 3 9H 2 O was dissolved in 100 mL of ultrapure water and dispersed by ultrasonic, which was recorded as mixed metal nitrate solution.

[0089] Finally, a Ni-Cu-Fe-In mesohex metallic compound catalyst is obtained, in which the molar ratio of Ni, Cu, Fe and In is 1:1:1:1.

[0090] Comparative Example 4: Preparation of Ni-Co-Fe-In Medium Entropy Intermetallic Compound Catalyst

[0091] The preparation method of this comparative example is basically the same as that of comparative example 1, except that:

[0092] In step (1), 0.8724 g Ni(NO 3 ) 2 6H 2 O, 0.8731 g Co(NO 3 ) 2 6H 2 O, 1.2117 gFe(NO 3 ) 3 9H 2 O, 0.9025g In(NO 3 ) 3 、11.5385g Mg(NO 3 ) 2 6H 2 O and 5.6270gAl(NO 3 ) 3 9H 2 O was dissolved in 100 mL of ultrapure water and dispersed by ultrasonic, which was recorded as mixed metal nitrate solution.

[0093] Finally, a Ni-Co-Fe-In mesohex metallic compound catalyst was obtained, in which the molar ratio of Ni, Co, Fe and In was 1:1:1:1.

[0094] Comparative Example 5: Preparation of Ni-Co-Cu-In Medium Entropy Intermetallic Compound Catalyst

[0095] The preparation method of this comparative example is basically the same as that of comparative example 1, except that:

[0096] In step (1), 0.8724 g Ni(NO 3 ) 2 6H 2 O, 0.8731 g Co(NO 3 ) 2 6H 2 O, 0.7248gCu(NO 3 ) 2 ·3H 2 O, 0.9025g In(NO 3 ) 3 、11.5385g Mg(NO 3 ) 2 6H 2 O and 5.6270gAl(NO 3 ) 3 9H 2 O was dissolved in 100 mL of ultrapure water and dispersed by ultrasonic, which was recorded as mixed metal nitrate solution.

[0097] Finally, a Ni-Co-Cu-In mesenterotropic intermetallic compound catalyst is obtained, in which the molar ratio of Ni, Co, Cu and In is 1:1:1:1.

[0098] Comparative Example 6: Preparation of Ni-Co-Cu-Fe Medium Entropy Intermetallic Compound Catalyst

[0099] The preparation method of this comparative example is basically the same as that of comparative example 1, except that:

[0100] In step (1), 0.8724 g Ni(NO 3 ) 2 6H 2 O, 0.8731 g Co(NO 3 ) 2 6H 2 O, 0.7248gCu(NO 3 ) 2 ·3H 2 O, 1.2117 g Fe(NO 3 ) 3 9H 2 O, 11.5385 g Mg(NO 3 ) 2 6H 2 O and 5.6270gAl(NO 3 ) 3 9H 2 O was dissolved in 100 mL of ultrapure water and dispersed by ultrasonic, which was recorded as mixed metal nitrate solution.

[0101] Finally, a Ni-Co-Cu-Fe mesohex metallic compound catalyst was obtained, in which the molar ratio of Ni, Co, Cu and Fe was 1:1:1:1.

[0102] Example 10: CO in a CO-rich atmosphere 2 Hydrogenation performance evaluation

[0103] The catalysts prepared in Examples 1 to 9 and Comparative Examples 1 to 6 were subjected to CO 2 Hydrogenation performance evaluation: The performance evaluation process was carried out on the ZKJC-RJ-X system of Beijing Wanlonghe Technology Co., Ltd., including:

[0104] The components in the reactants and products were analyzed online using a 3-channel GC9790Plus (Fuli Company, China).

[0105] The chromatograph is equipped with two detectors: a thermal conductivity detector (TCD) with GDX-01 and GDX-02 columns for detecting H 2 , CO, CH 4 and CO 2 The second is a hydrogen flame ionization detector (FID) equipped with an RB-INNOWAX column, which is used to analyze hydrocarbons. Combined with the external standard method, the concentration of each component in the product can be accurately determined.

[0106] Evaluation conditions: total inlet flow rate 60mL / min; raw gas 25% CO, 5% CO 2 , 65% H 2 and 5% N 2 ; Reaction temperature is 240℃; Pressure is 4MPa; Catalyst loading is 150mg.

[0107] The specific performance evaluation steps are as follows:

[0108] Weigh 150 mg of catalyst sample, mix it evenly with 350 mg of quartz sand, and then load it into the constant temperature zone of the stainless steel reaction tube. After the catalyst is loaded, first check the reaction system for leaks. Pass a certain pressure of N into the reaction system. 2 (such as 1Mpa). If the pressure remains unchanged, it means that the system is well sealed and performance evaluation can be carried out.

[0109] Setting N 2 The flow rate was 20 sccm (Standard Cubic Centimeter Per Minute), and the temperature was raised to the reduction temperature; then N 2 , switch to H 2 The flow rate is 20sccm, and the H is turned off after a certain period of reduction. 2 ; Then switch N 2The flow rate is 20sccm, the temperature is lowered to the reaction temperature, and the pressure required for the reaction is set. After the reaction conditions are stable, the flow rate of each reaction component is set, and the furnace six-way valve is switched to bypass, so that the mixed gas directly enters the chromatograph to detect the concentration of each component before the reaction. After stabilization, the furnace six-way valve is switched back to the reaction tube to start the reaction, and the concentration of each component in the gas at the outlet of the reaction tube is detected by chromatography.

[0110] The reaction equation in this test is as follows:

[0111] CO 2 +3H 2 =CH 3 OH+H 2 O

[0112] CO+2H 2 =CH 3 OH

[0113] The carbon monoxide conversion rate C(CO) and carbon dioxide conversion rate C(CO) of the catalysts prepared in Examples 1 to 9 and Comparative Examples 1 to 6 were tested. 2 ) and methanol selectivity S(CH 3 OH) to evaluate the CO performance of the catalyst in a CO-rich atmosphere 2 Catalytic performance of the hydrogenation reaction to methanol, including:

[0114]

[0115] The catalytic performance evaluation results of the catalysts prepared in Examples 1 to 9 and Comparative Examples 1 to 6 at 240° C. are shown in Table 1 below:

[0116] Table 1

[0117] Example Catalyst element composition Element molar ratio C(CO) / % <![CDATA[C(CO 2 ) / %]]> <![CDATA[S(CH 3 OH) / %]]> Example 1 Ni-Co-Cu-Fe-In-Zn 1:1:1:1:1:1 82.14 10.32 98.79 Example 2 Ni-Co-Cu-Fe-In-Mo 1:1:1:1:1:1 79.94 11.05 99.10 Example 3 Ni-Co-Cu-Fe-In-Ce 1:1:1:1:1:1 80.93 10.68 98.82 Example 4 Ni-Co-Cu-Fe-In-Zn 1:0.9:0.9:0.9:0.9:0.9 77.49 9.16 95.17 Example 5 Ni-Co-Cu-Fe-In-Mo 1:0.9:0.9:0.9:0.9:0.9 76.35 10.08 96.67 Example 6 Ni-Co-Cu-Fe-In-Ce 1:0.9:0.9:0.9:0.9:0.9 77.93 9.77 97.31 Example 7 Ni-Co-Cu-Fe-In-Zn 1:1.1:1.1:1.1:1.1:1.1 78.21 8.98 97.82 Example 8 Ni-Co-Cu-Fe-In-Mo 1:1.1:1.1:1.1:1.1:1.1 77.39 9.66 96.83 Example 9 Ni-Co-Cu-Fe-In-Ce 1:1.1:1.1:1.1:1.1:1.1 76.47 9.41 96.22 Comparative Example 1 Ni-Co-Cu-Fe-In 1:1:1:1:1 79.47 10.44 98.23 Comparative Example 2 Co-Cu-Fe-In 1:1:1:1 42.61 7.88 79.26 Comparative Example 3 Ni-Cu-Fe-In 1:1:1:1 56.33 6.44 82.15 Comparative Example 4 Ni-Co-Fe-In 1:1:1:1 28.24 6.07 66.38 Comparative Example 5 Ni-Co-Cu-In 1:1:1:1 46.97 7.09 70.94 Comparative Example 6 Ni-Co-Cu-Fe 1:1:1:1 63.49 8.33 87.62

[0118] From the results in Table 1, it can be seen that the Ni-Co-Cu-Fe-In five-element high entropy intermetallic compound catalyst prepared in Comparative Example 1 exhibits excellent conversion rate and selectivity, indicating that the element composition is CO in a CO-rich atmosphere. 2 It has significant advantages in the hydrogenation reaction to produce methanol.

[0119] Comparative Examples 2 to 6 prepared medium-entropy metal compound catalysts without Ni, Co, Cu, Fe and In elements, respectively, and all showed varying degrees of performance degradation, indicating that the excellent CO resistance of this series of catalysts originates from the synergistic effect between Ni, Co, Cu, Fe and In elements.

[0120] The Ni-Co-Cu-Fe-In-M hexavalent high entropy intermetallic compound catalysts prepared by introducing M (Zn, Mo or Ce) elements in Examples 1 to 3 have no significant improvement in conversion rate and selectivity compared with the catalyst in Comparative Example 1, indicating that the M element has a significant effect on the reactants (CO, CO2, H2) and products (CH 3 The effect on the adsorption and desorption capacity of OH) molecules is small and can be almost ignored.

[0121] In summary, the CO resistance of this series of catalysts is mainly due to the synergistic effect between Ni, Co, Cu, Fe and In elements. It is easy for those skilled in the art to understand that different elements in high entropy metal intermetallic compound catalysts can play different roles in the catalytic reaction. Some elements can activate specific reactants or intermediates, while other elements are responsible for stabilizing the reaction products or intermediates. This series of catalysts, CO in a CO-rich atmosphere 2 In hydrogenation reactions, Cu is good at activating H 2 , Ni, Co and Fe can promote the 2 The adsorption and decomposition of the active metals can produce a synergistic effect in the catalytic process, thereby improving the overall efficiency and selectivity of the reaction. Although the inert metal In does not directly participate in the catalytic process, it can improve the isolation between active metals to a certain extent, optimize the geometric structure and electronic structure of the active sites, and thus improve the catalytic performance.

[0122] On the other hand, by comparing the test results of Examples 1 to 3 and 4 to 9, it is found that adjusting the ratio of elements in the catalyst (less than 1: Examples 4 to 6; greater than 1: Examples 7 to 9) will lead to a slight decrease in catalytic performance. This shows that during the catalyst preparation process, strictly controlling the ratio between elements to 1 is helpful to achieve the best catalytic effect of this series of catalysts.

[0123] Example 11, containing H 2 CO in S atmosphere 2 Hydrogenation stability evaluation

[0124] The sulfur resistance of the high entropy intermetallic compound catalysts prepared in Examples 1 to 3 and Comparative Example 1 was evaluated. 2 S, and the rest of the operations are consistent with the performance evaluation steps of the above-mentioned embodiment 10.

[0125] Evaluation conditions: total inlet flow rate 60mL / min; raw gas 20ppm H 2 S, 25% CO, 5% CO 2 , 65% H 2 and 5% N 2 ; Reaction temperature is 240℃; Pressure is 4MPa; Catalyst loading is 150mg.

[0126] according to Figures 2 to 4 This series of catalysts can still maintain good catalytic activity during the reaction process of up to 60 hours, and the CO conversion rate and CO 2 Conversion rate and CH 3 The OH selectivity was maintained at about 77%, 9% and 97% respectively. Figure 5 As shown in the figure, the Ni-Co-Cu-Fe-In five-element high entropy metal intermetallic compound catalyst prepared in Comparative Example 1 showed a significant performance decline in the early stage of the stability test. And only after about 15 hours of reaction, the CO conversion rate and CO 2 Conversion rate and CH 3 The OH selectivity dropped to 18%, 1.5% and 10% respectively, indicating that the catalyst has been deactivated. In contrast, the Ni-Co-Cu-Fe-In-M hexavalent high entropy metal compound catalyst prepared in Examples 1 to 3 exhibited excellent anti-sulfur performance. This shows that the introduction of anti-sulfur additive element M (such as Zn, Mo or Ce) significantly enhances the anti-sulfur performance of the catalyst. The present invention effectively improves its anti-sulfur ability by introducing additive elements into the high entropy metal compound catalyst, demonstrating the great potential of this design in the industrial application of green methanol synthesis catalysts.

[0127] It should be noted that the above-described embodiments should be understood as illustrative rather than limiting the scope of protection of the present invention. For those skilled in the art, non-essential improvements and adjustments made to the present invention without departing from the essence and scope of the present invention still fall within the scope of protection of the present invention.

Claims

1. A sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst, characterized in that: The catalyst is a Ni-Co-Cu-Fe-In-M high entropy intermetallic compound catalyst obtained by loading a Ni-Co-Cu-Fe-In-M hexametallic compound on an aluminum-magnesium metal mixed oxide; Among them, Ni, Co, Cu and Fe are active metals, In is an inert metal, and M is a sulfur-resistant metal selected from one of Zn, Mo and Ce; The molar ratio of the metals Ni, Co, Cu, Fe, In, M, Mg and Al in the catalyst is 1:(0.9-1.1):(0.9-1.1):(0.9-1.1):(0.9-1.1):(0.9-1.1):(14-16):(4-6), preferably 1:1:1:1:1:1:(14-16):(4-6).

2. The method for preparing the sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst according to claim 1, characterized in that: The following steps are involved: (1) Preparation of Ni / Co / Cu / Fe / In / M / Mg / Al octal layered hydroxide When M is Zn or Ce, nitrates of Ni, Co, Cu, Fe, In, M, Mg and Al are prepared into a mixed metal nitrate solution in proportion, and then a Ni / Co / Cu / Fe / In / M / Mg / Al octal layered hydroxide is prepared by a coprecipitation method; When M is Mo, nitrates of Ni, Co, Cu, Fe, In, Mg and Al are prepared into a mixed metal nitrate solution in proportion, and a Ni / Co / Cu / Fe / In / Mg / Al seven-membered layered hydroxide is prepared by a coprecipitation method; then a Mo precursor solution is added to the seven-membered layered hydroxide for ion exchange to prepare a Ni / Co / Cu / Fe / In / M / Mg / Al eight-membered layered hydroxide; (2) The Ni / Co / Cu / Fe / In / M / Mg / Al octa-layered hydroxide in step (1) is filtered, washed and dried, and then subjected to thermal reduction treatment to obtain a sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst.

3. The method for preparing the sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst according to claim 2, characterized in that: In step (1), when M is Zn or Ce, the molar ratio of Ni, Co, Cu, Fe, In, M, Mg and Al ions in the mixed metal nitrate solution is 1:(0.9-1.1):(0.9-1.1):(0.9-1.1):(0.9-1.1):(0.9-1.1):(14-16):(4-6); preferably, the molar ratio of Ni, Co, Cu, Fe, In, M, Mg and Al ions in the mixed metal nitrate solution is 1:1:1:1:1:1:(14-16):(4-6); When M is Mo, the molar ratio of Ni, Co, Cu, Fe, In, Mg and Al ions in the mixed metal nitrate solution is 1:(0.9-1.1):(0.9-1.1):(0.9-1.1):(0.9-1.1):(14-16):(4-6); preferably, the molar ratio of Ni, Co, Cu, Fe, In, Mg and Al ions in the mixed metal nitrate solution is 1:1:1:1:1:(14-16):(4-6); the molar ratio of Ni ions in the mixed metal nitrate solution to molybdate ions in the Mo precursor solution is 1:(0.9-1.1).

4. The method for preparing the sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst according to claim 2, characterized in that: In step (1), the nitrates of Ni, Co, Cu, Fe, In, Zn, Ce, Mg and Al are Ni(NO3)2·6H2O, Co(NO3)2·6H2O, Cu(NO3)2·3H2O, Fe(NO3)3·9H2O, In(NO3)3, Zn(NO3)2·6H2O, Ce(NO3)2·6H2O, Mg(NO3)2·6H2O and Al(NO3)3·9H2O respectively; the Mo precursor is selected from one of Na2MoO4, K2MoO4 or (NH4)2MoO4; In the mixed metal nitrate solution, the concentration of Mg ions is 0.40-0.65 mol / L; in the Mo precursor solution, the concentration of Mo ions is 0.08-0.12 mol / L.

5. The method for preparing the sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst according to claim 2, characterized in that: Step (1) specifically includes the following steps: Under stirring conditions, when M is Zn or Ce, a mixed metal nitrate solution is added to the precipitant, or when M is Mo, a mixed metal nitrate solution and a Mo precursor solution are added to the precipitant in sequence, the feeding rate is controlled to be 0.8-1.2 mL / min, the temperature of the reaction system is controlled to be 60-70° C., and the pH value of the reaction system is controlled to be 10±1 by a pH regulator; after the feeding is completed, the stirring reaction is continued for 15-20 hours to obtain the Ni / Co / Cu / Fe / In / M / Mg / Al octal layered hydroxide.

6. The method for preparing the sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst according to claim 5, characterized in that: The precipitant is selected from one of Na2CO3 solution, NaHCO3 solution or K2CO3 solution; the molar concentration of the precipitant is 0.3-0.5 mol / L.

7. The method for preparing the sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst according to claim 5, characterized in that: The pH regulator is selected from one of NaOH solution and KOH solution; the molar concentration of the pH regulator is 1.8-2.0 mol / L.

8. The method for preparing the sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst according to claim 2, characterized in that: In step (2), the drying conditions are: 90-110°C, drying for 12-20 hours; the thermal reduction treatment conditions are: in a mixed atmosphere of H2 and Ar, 700-900°C, reduction for 3-5 hours.

9. Use of the sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst according to claim 1 or the sulfur-resistant and CO-resistant high-entropy intermetallic compound catalyst prepared by the preparation method according to any one of claims 2 to 8, characterized in that: Used for the catalytic hydrogenation of CO2 to produce methanol in a CO-rich atmosphere.

10. The use according to claim 9, characterized in that: The catalytic reaction conditions are as follows: the raw gas includes 15-25 ppm H2S, 23-27% CO, 4-6% CO2, 64-66% H2, and the remaining gas is N2; the reaction temperature is 200-300°C; and the pressure is 3-5MPa.

Citation Information

Cited By

  • Sulfur-resistant moisture-proof CO oxidation regular-structure catalyst as well as preparation method and application thereof

    CN121551025A

  • A sulfur-resistant and moisture-resistant CO oxidation regular structure catalyst, a preparation method and application thereof

    CN121551025B

  • Green methanol synthesis process and system based on biogas

    CN121913870A